Developing the models of patterns in the design of requirements to an information system at the knowledge level - Levykin, Viktor; Ievlanov, Maksym; Neumyvakina, Olga (Eastern-European Journal of Enterprise Technologies, 2017)
Results of research into mining and processing of knowledge from IS requirements were analyzed. Modification of the frame-based model of knowledge that allows description of knowledge about structures of data and interaction processes is considered. The essence of modification is to extend the frame with descriptions of a totality of methods, associated with a frame as a whole, as well as descriptions of interfaces of a frame. This modification also makes it possible in a formalized way to describe the problem of automated synthesis of IS information and software as a set of one-to-one mappings of frame descriptions. Theoretical-multiple models of structural IS requirements design patterns at the knowledge level were developed. These models allow describing the knowledge, derived from IS requirements descriptions in the form of a network of frames. This network consists of individual frames, interfaces of frames and relationships between them. The use of these models makes it possible to formalize the process of designing of IS architecture based on knowledge, derived from IS requirements descriptions, which significantly reduces the time spent on IS creation. Theoretical-multiple models of behavioral IS requirements design patterns at the knowledge level were developed. These models establish the main features of operations of addition, modifications and deletion of elements of structural IS requirements design patterns. In addition, developed models describe operations on formation of knowledge-oriented descriptions of IS architecture in the form of a network of frames and interfaces. Application of these models enables us to standardize implementation of operations on the knowledge, derived from patterns, and on patterns of designing structural frames. It was proposed to consider implementation of the developed models in the form of specialized data showcases and sets of SQL-commands that implement developed behavioral patterns.